2006
DOI: 10.1073/pnas.0608319103
|View full text |Cite
|
Sign up to set email alerts
|

Concatenated logic gates using four coupled biocatalysts operating in series

Abstract: The assembly of three concatenated enzyme-based logic gates consisting of OR, AND, XOR is described. Four biocatalysts, acetylcholine esterase, choline oxidase, microperoxidase-11, and the NAD ؉ -dependent glucose dehydrogenase, are used to assemble the gates. Four inputs that include acetylcholine, butyrylcholine, O2, and glucose are used to drive the concatenated-gates system. The cofactor NAD ؉ , and its reduced 1,4-dihydro form, NADH, are used as a reporter couple, and these provide an optical output for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
166
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(167 citation statements)
references
References 24 publications
1
166
0
Order By: Relevance
“…29,30 Longer-term, however, the problem of "analog" noise reduction in biochemical logic should be considered within a broader context: Our present study has identified the source of the difficulty as follows. Gate optimization involves modification of the gate function, z = F(x,y), which changes the slope of various cross-sections of this function, some of which were marked in Figure 4(B).…”
Section: Conclusion and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…29,30 Longer-term, however, the problem of "analog" noise reduction in biochemical logic should be considered within a broader context: Our present study has identified the source of the difficulty as follows. Gate optimization involves modification of the gate function, z = F(x,y), which changes the slope of various cross-sections of this function, some of which were marked in Figure 4(B).…”
Section: Conclusion and Discussionmentioning
confidence: 93%
“…Using the advantages of enzyme-based logic gates, biocomputing "devices" such as a biomolecular half-adder, a half-subtractor 28 and keypad lock 29 were assembled to demonstrate systems with computational functionality composed of several concatenated logic gates. 29,30 1.2. Motivation.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10] In parallel, several groups have shown that it is possible realize complex combinational logic circuits at the molecular scale, up to half and full addition or subtraction using various external perturbations, i.e., chemical, biochemical, photochemical, optical, electrochemical, electrical, to address the system, encode the inputs and perform the logic operations. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] We propose here another approach for implementing molecular logic gates.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Willner, Katz and their colleagues combine acetylcholine esterase, choline oxidase, microperoxidase and glucose dehydrogenase to achieve the minimized gate array shown in Figure 7. 94 The 85 selectivity of acetylcholine esterase is not so extreme. So it hydrolyzes acetylcholine and butyrylcholine with comparable efficiency in an OR logical manner.…”
Section: Molecular Logic Gate Arrays Of Increasing Complexity Are Accmentioning
confidence: 99%